Evolution on the solid urban waste management in Brazil: A portrait of the Northeast Region - I. M. Costa; Marta Ferreira Dias (Energy Reports, 2020)
The discussion on the management of urban solid waste gained global contours in the 70's, but its interest in some developing countries is relatively recent. Namely in Brazil, the legislation was only approved in 2010 (Law 12,305). Almost 10 years after the approval of this policy instrument, a low evolution is identified with regard to the 4 basic management processes (generation, collection, selective collection and final disposal of waste). The impacts of inefficient management offer irreparable damage to the environment, including the uncontrolled emission of gases such as methane (CH4) which, although one of the main responsible for global warming, has great potential for electricity generation. Although Brazil already has technologies for power generation, the exploration of this sector, as well as others aimed at reuse, depend directly on the efficiency of the basic waste management processes. This paper aims discussing the evolution on the characterization of Urban Solid Waste Management - USWM in the Northeast Region of Brazil in a period from 2007 to 2017. The results and conclusion show the low application of the more recent legislation (deliberations of Law 12,305) on the Northeast Region, materialized on the low effectiveness in the processes, as well as the small evolution concerning the guidelines of the National Waste Plan of the year 2012 and the present objectives in the Agenda 2030 for Sustainable Development published by the United Nations Organization in 2015. The identified scenario points to the urgent need to fill the gaps in the Northeast, in order to make legislation more effective, reduce environmental impacts and boost waste reuse sectors.
Keywords: 330; Brazil; Characterization; Northeast Region; Solid waste management